Design considerations for an eHealth decision support tool in inflammatory bowel disease self‐management. Issue 6 (12th June 2018) - Jackson, Belinda D.; Con, Danny; De Cruz, Peter
Abstract: Background: Electronic health (eHealth) decision support tools have the potential to: facilitate inflammatory bowel disease (IBD) self‐management, reduce health care utilisation and alleviate the pressure on overburdened outpatient clinics. The purpose of this study was to explore the perspectives of key stakeholders on the potential use of a decision support tool for IBD patients. Methods: A qualitative study using focus group methodology was conducted at a tertiary IBD centre in Melbourne, Australia in February 2015. Key stakeholders, including physicians, nurses and patients, were included in the study. Two independent reviewers undertook inductive coding and generated themes. Results: In total, 31 participants were included in the study (including 16 males; 11 physicians; 6 nurses). An eHealth decision support tool was thought to be beneficial to facilitate IBD self‐management. Four themes emerged: (i) Framework for the decision support tool – the tool should be an adjunct to current models of care and facilitate shared decision‐making and patient engagement; (ii) Target population – stable patients with mild to moderate disease; (iii) Functionalities of the intervention – a web‐based platform encompassing patient‐reported outcomes, objective markers of disease and clinical algorithms based on international guidelines; and (iv) Design and Implementation – patients should be involved in the design. Conclusions: eHealth interventions are thought to be an important strategy to facilitate self‐management for patients with IBD. A multi‐stage iterative approach should be adopted in the design and implementation process of eHealth interventions. Patient perspectives need to be sought prior to and throughout the development of an eHealth decision support tools for IBD.